Design of SGLT2 Inhibitors for the Treatment of Type 2 Diabetes: A History Driven by Biology to Chemistry - Cai, Wenqing; Jiang, Linlin; Xie, Yafei; Liu, Yuqiang; Liu, Wei; Zhao, Guilong (Medicinal Chemistry, 2015)
A brief history of the design of sodium-dependent glucose cotransporter 2 (SGLT2) inhibitors is reviewed. The design of O-glucoside SGLT2 inhibitors by structural modification of phlorizin, a naturally occurring O-glucoside, in the early stage was a process mainly driven by biology with anticipation of improving SGLT2/SGLT1 selectivity and increasing metabolic stability. Discovery of dapagliflozin, a pioneering C-glucoside SGLT2 inhibitor developed by Bristol-Myers Squibb, represents an important milestone in this history. In the second stage, the design of C-glycoside SGLT2 inhibitors by modifications of the aglycone and glucose moiety of dapagliflozin, an original structural template for almost all C-glycoside SGLT2 inhibitors, was mainly driven by synthetic organic chemistry due to the challenge of designing dapagliflozin derivatives that are patentable, biologically active and synthetically accessible. Structure-activity relationships (SAR) of the SGLT2 inhibitors are also discussed.
Keywords: type 2 diabetes